Dysphagia due to Diffuse Idiopathic Skeletal Hyperostosis - Masafumi Ohki (Case Reports in Otolaryngology)
Diffuse idiopathic skeletal hyperostosis (DISH) is usually asymptomatic. However, rarely, it causes dysphagia, hoarseness, dyspnea, snoring, stridor, and laryngeal edema. Herein, we present a patient with DISH causing dysphagia. A 70-year-old man presented with a 4-month history of sore throat, dysphagia, and foreign body sensation. Flexible laryngoscopy revealed a leftward-protruding posterior wall in the hypopharynx. Computed tomography and magnetic resonance imaging revealed a bony mass pushing, anteriorly, on the posterior hypopharyngeal wall. Ossification included an osseous bridge involving 5 contiguous vertebral bodies. Dysphagia due to DISH was diagnosed. His symptoms were relieved by conservative therapy using anti-inflammatory drugs. However, if conservative therapy fails and symptoms are severe, surgical treatments must be considered.